신생아중환자의 약동학적 다양성에 영향을 미치는 요인 - 안숙희; An, Sook Hee (한국임상약학회지, 2017)
Neonates have large inter-individual variability in pharmacokinetic parameters of many drugs due to developmental differences. The aim of this study was to investigate the factors affecting the pharmacokinetic parameters of drugs, which are commonly used in critically ill neonates. Factors that reflect physiologic maturation such as gestational age, postnatal age, postconceptional age, birth weight, and current body weight were correlated with pharmacokinetic parameters in neonates, especially preterm infants. Comorbidity characteristics affecting pharmacokinetics in critically ill neonates were perinatal asphyxia, hypoxic ischemic encephalopathy, patent ductus arteriosus (PDA), and renal dysfunction. Administration of indomethacin or ibuprofen in neonates with PDA was associated with the reduced clearance of renally excreted drugs such as vancomycin and amikacin. Therapeutic hypothermia and extracoporeal membrane oxygenation were influencing factors on pharmacokinetic parameters in critically ill neonates. Dosing adjustment and careful monitoring according to the factors affecting pharmacokinetic variability is required for safe and effective pharmacotherapy in neonatal intensive care unit.